OP0309 OPTIMIZATION OF FLARE MANAGEMENT IN PATIENTS WITH RHEUMATOID ARTHRITIS: RESULTS OF A RANDOMIZED CONTROLLED TRIAL. (June 2019) - Myasoedova, Elena; Crowson, Cynthia S.; Giblon, Rachel; Schaffer, Daniel; Wright, Kerry; Matteson, Eric; Davis, John
Abstract : Background: Flares in rheumatoid arthritis (RA) are common [1]. The shortage of readily available specialized care may hinder early detection and timely management of RA flares. Engaging non-physician rheumatology providers in care of RA flares may be beneficial. Objectives: To evaluate the effect of a nurse-led flare management intervention versus usual care between rheumatology visits on flare occurrence and RA disease activity in patients with RA. Methods: Patients with established RA (2010 ACR criteria) were randomized to the intervention versus usual care. The Flare Assessment in Rheumatoid Arthritis (FLARE-RA) questionnaire was administered monthly during the 24-month follow-up to all patients in the intervention arm to assess flare status. The results of the FLARE-RA questionnaire and patient's response to the question "Are you currently in a flare of your RA?" were recorded. Telephone nurse-led counseling or a visit with a mid-level rheumatology provider within 7 days of detection of flare was offered to patients in the intervention arm who indicated they were in flare. Patients in the usual care arm were followed by their rheumatology providers according to standards of care. OMERACT9 definition of flare was used to compare flare occurrence between the study arms. All patients completed satisfaction surveys at baseline and at the end of the follow-up. Results: 150 patients with RA were randomized to intervention (n=75) versus usual care (n=75). At baseline, the majority of patients in the intervention arm (51%) and in the usual care (60%, p=0.32) were interested in expedited appointments with a rheumatology provider if in RA flare. There were no differences between the study arms at baseline in age, sex, tender joint counts, pain intensity, patient and physician global assessments, C-reactive protein levels, DAS28-CRP, CDAI, or SDAI. Despite randomization, patients in the intervention arm had lower swollen joint counts (1.1±2.7 vs 2.4, p=0.003) and Health Assessment Questionnaire (HAQ) score (0.6±0.6 vs 0.9±0.6, p=0.005) than those in the usual care arm. The number of patients in the intervention arm who completed the FLARE-RA questionnaires at baseline, 6, 12, 18, and 24 months was 75, 37, 27, 13, and 23, respectively. Patients in the intervention arm completed a median of 8.5 (range 1-24) questionnaires. RA flare was reported on 122 (19%) of these questionnaires; average FLARE-RA score: 2.57. Patients agreed to have an expedited clinic visit with a rheumatology provider during 39 (32%) of flares. The majority of patients preferred to self-manage their flare (76, 62%) or receive nursing advice over the phone 7 (6%). There were no differences in DAS28-CRP, CDAI, SDAI, anti-rheumatic treatment change by rheumatology provider, RA flare by OMERACT9 definition, or remission by CDAI between the study arms over 24-month follow-up. At the end of the study, a higher proportion of patients in the intervention arm (44%) versus the usual care arm (21%, p=0.04) reported positive effect of participation in the study on the management of RA flares. Conclusion: The majority of patients expressed interest in expedited rheumatology appointments for their RA flares on their baseline patient-satisfaction survey. However, during the study, patients in the intervention arm largely preferred self-management and/or over-the-phone counseling. The nurse-led flare management intervention had no major effect on RA disease activity metrics over the 24-month follow-up. However, patients in the intervention arm reported a positive effect of the intervention. More studies are needed to further understand patient preferences for optimal RA flare management and to design interventions to meaningfully address these preferences. Reference: [1] Bechman, K., et al. J Rheumatol, 2018. 45(11): p. 1515-21. Disclosure of Interests: Elena Myasoedova Grant/research support from: Pfizer, Cynthia S. Crowson: None declared, Rachel Giblon: None declared, Daniel Schaffer: None declared, Kerry Wright: None declared, Eric Matteson Grant/research support from: Eric Matteson has received research grants from Pfizer and Sun Pharmaceutical Industries, Ltd. for work on the pathobiology of rheumatoid arthritis., Consultant for: Eric Matteson has received consultancy fees from Boehringer Ingelheim for an advisory board., John Davis Grant/research support from: Pfizer